Convenient and efficient synthesis of novel 11H-benzo[5, 6][1, 4]thiazino[3, 4-a]isoindol-11-ones derived from 2-bromo-(2/3-substitutedphenyl)-1H-indene-1, 3(2H)-diones. Issue 23 (25th April 2019) - Mor, Satbir; Sindhu, Suchita
Abstract : A metal-free and convenient approach to the synthesis of novel 11 H -benzo[5, 6][1, 4]thiazino[3, 4- a ]isoindol-11-ones (5 ) is described. Abstract : An unprecedented formation of 11 H -benzo[5, 6][1, 4]thiazino[3, 4- a ]isoindol-11-ones through a one-step reaction of differently substituted 2-aminobenzenethiols and 2-bromo-(2/3-substitutedphenyl)-1 H -indene-1, 3(2 H )-diones in freshly dried ethanol under reflux conditions has been investigated. This unique transformation probably occurs through an initial nucleophilic substitution followed by ring opening and subsequent intramolecular cyclization. The structures of all the synthesized benzo[1, 4]thiazino isoindolinones were established by FTIR, 1 H NMR, 13 C NMR, HRMS, and X-ray crystallographic analysis. This approach was found to be simple and convenient and provides several advantages such as substantial atom economy, short reaction time and operational simplicity.